DEVELOPMENT OF COMIC-BASED MATHEMATICS LEARNING MEDIA ON MATERIAL OF 3D CUBE SIDE WITH A SCIENTIFIC APPROACH FOR 9TH GRADE SMP/MTS - Rizki Dera Amanda; Suhendra Suhendra; Syariful Fahmi (Prima: Jurnal Pendidikan Matematika, 2026)
Math subjects are subjects that are often difficult for learners. Poor media and learning resources during the learning process greatly influence the results of learning. A varied medium of learning is urgently needed to help the learning process. One of the learning media that can help the learning process is the comic-based learning medium. The study aims to develop a comic-based medium of learning-room material that is particularly worthy of use in the learning process. The study is a development study using addie's model: analysis, design, development, improvement, and design. The subject of this study is a material expert, a media expert, and students of SMPN 2 Mendo Barat. The data-collection techniques used in the study include interviews, questionnaires, and observations. The data obtained from the questionnaire were analyzed descriptively qualitative and quantitative. As a result of the study, the developed media of learning is deemed to be particularly useful in the mathematical learning process. This is shown with the result of a dose of the learning media This is demonstrated by the overall assessments of the learning media and get an excellent category by an average of 3.60. Each assessment results from a material expert who got an excellent category with an average of 3.50, from a media expert who got an excellent category with an average of 3.88, from a learner's response that got an excellent category with an average of 3.38 in the small class trials and 3.64 in the large class trials.